Effects of body mass index on IVF outcomes in different age groups - Dan Liu; Li Li; Ningyu Sun; Xiaole Zhang; Ping Yin; Wuwen Zhang; Panwei Hu; Hua Yan; Qinhua Zhang (BMC, 2023)
Abstract Background Herein, we aimed to analyse the effects of body mass index (BMI) on the treatment outcomes of in vitro fertilisation (IVF) in a cohort of women undergoing their first IVF cycle. Methods A total of 2311 cycles from 986 women undergoing their first IVF/intracytoplasmic sperm injection cycle with fresh/frozen embryo transfer between January 2018 and December 2021 at the Center of Reproductive Medicine, Shuguang Hospital affiliated to Shanghai University of Traditional Chinese Medicine, were considered in this retrospective cohort study. First, the included patients were classified into four groups based on their BMI: underweight (BMI < 18.5 kg/m2, 78 patients), normal weight (18.5 ≤ BMI < 24 kg/m2, 721patients), overweight (24 ≤ BMI < 28 kg/m2, 147 patients), and obese (BMI ≥ 28 kg/m2, 40 patients). The IVF outcomes included the Gn medication days; Gn dosage; number of retrieved oocytes, mature oocytes, fertilized oocytes, cleavages, and available embryos and high-quality embryos; implantation rate; clinical pregnancy rate and live birth rate. Next, all the obtained data were segregated into three different subgroups according to the patient age: < 30 years, 30-38 years and > 38 years; the IVF pregnancy outcomes were compared among the groups. Results Compared with the other three groups, the underweight group had a higher number of fertilized oocytes, cleavage and available embryos and a smaller Gn medication days and required a lower Gn dosage. There was no difference in the number of retrieved oocytes and mature oocytes among the groups. Moreover, compared with the women aged 30-38 years in the overweight group, those in the normal weight group had a significantly higher implantation rate, clinical pregnancy rate and live birth rate (p = 0.013 OR 1.75, p = 0.033 OR 1.735, p = 0.020 OR 1.252 respectively). The clinical pregnancy rate was also significantly higher in those aged 30-38 years in the normal weight group than in the obese group (p = 0.036 OR 4.236). Conclusions Although the BMI can greatly affect the pregnancy outcomes of women aged 30-38 years, it has almost no effects on the outcomes of younger or older women.